Safety and maintenance of response for tofacitinib monotherapy and combination therapy in rheumatoid arthritis: an analysis of pooled data from open-label long-term extension studies. Issue 2 (18th December 2017) - Fleischmann, Roy; Wollenhaupt, Jürgen; Takiya, Liza; Maniccia, Anna; Kwok, Kenneth; Wang, Lisy; van Vollenhoven, Ronald F
Abstract : Objective: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis. This post hoc analysis evaluated patients receiving tofacitinib monotherapy or combination therapy, as well as those who switched from monotherapy to combination therapy (mono→combo) or vice versa (combo→mono) in long-term extension (LTE) studies. Methods: Data were pooled from open-label LTE studies (ORAL Sequel (NCT00413699 ; ongoing; data collected 14 January 2016) and NCT00661661 ) involving patients who participated in qualifying index studies. Efficacy outcomes included American College of Rheumatology 20/50/70 rates, change from baseline in Disease Activity Score in 28 joints, erythrocyte sedimentation rate (DAS28-4(ESR)), Clinical Disease Activity Index (CDAI) and Health Assessment Questionnaire-Disability Index and DAS28-4(ESR) and CDAI low disease activity and remission. Safety was evaluated over 96 months. Results: Of the 4967 patients treated, 35.4% initiated tofacitinib monotherapy, 64.6% initiated combination therapy, 2.6% were mono→combo switchers and 7.1% were combo→mono switchers. Patients who switched multiple times were excluded. Of those who initiated monotherapy and combination therapy, 87.8% (1543/1757) and 82.0% (2631/3210), respectively, remained on the same regimen throughout the study; efficacy was maintained. Incidence rates (IRs) for serious adverse events with tofacitinib 5 mg and 10 mg twice daily, respectively, were 9.42 and 8.41 with monotherapy and 8.36 and 10.75 with combination therapy; IRs for discontinuations due to AEs were 7.13 and 6.06 with monotherapy and 7.82 and 8.06 with combination therapy (overlapping CIs). For mono→combo and combo→mono switchers, discontinuations due to AEs were experienced by 0.8% and 0.9%, respectively, within 30 days of switching. Conclusion: Tofacitinib efficacy as monotherapy or combination therapy was maintained through month 48 and sustained to month 72, with minimal switching of treatment regimens. Safety was consistent over 96 months. Clinical trial registration: NCT00413699 (Pre-results) and NCT00661661 (Results).